Cover Feature: Flow‐Based Deacidification of Geobacter sulfurreducens Biofilms Depends on Nutrient Conditions: a Microfluidic Bioelectrochemical Study (ChemElectroChem 23/2018). Issue 23 (30th October 2018) - Zarabadi, Mir Pouyan; Charette, Steve J.; Greener, Jesse
Abstract : The Cover Feature illustrates biofilms from Geobacter sulfurreducens that are examined in a microfluidic electrochemical system. Changes to biofilm pH are measured in situ while modulating hydrodynamic turnover, nutrient‐limited, and starvation conditions. Increased flow rates can mitigate biofilm acidification, but not under turnover concentrations. More information can be found in the Article by M. P. Zarabadi et al. onpage 3645 in Issue 23, 2018 (DOI:10.1002/celc.201800968 ).